2015
DOI: 10.1186/s13148-015-0113-1
|View full text |Cite
|
Sign up to set email alerts
|

A varying T cell subtype explains apparent tobacco smoking induced single CpG hypomethylation in whole blood

Abstract: BackgroundMany recent epigenetic studies report that cigarette smoking reduces DNA methylation in whole blood at the single CpG site cg19859270 within the GPR15 gene.ResultsWithin two independent cohorts, we confirmed the differentially expression of the GPR15 gene when smokers and non-smokers subjects are compared. By validating the GPR15 protein expression at the cellular level, we found that the observed decreased methylation at this site in white blood cells (WBC) of smokers is mainly caused by the high pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 29 publications
4
70
0
2
Order By: Relevance
“…15 It is worth to note that the significant difference in methylation status of genes found in the peripheral blood of breast cancer patients may be affected by the change in population of different types of WBCs as previously described by the effects of tobacco on peripheral blood hypomethylation. 72 Nonetheless, we found some hypermethylated genes in WBCs of breast cancer patients including APC, HDAC1, BRCA1, and GSK1 whose hypermethylation pattern has been previously reported in more than one studies of breast cancer tissues. Replication of the same gene methylation pattern in different sample types and patients' race may highlight the critical epigenetic changes of those genes toward their under-expression leading to cancer progression.…”
Section: Discussionmentioning
confidence: 89%
“…15 It is worth to note that the significant difference in methylation status of genes found in the peripheral blood of breast cancer patients may be affected by the change in population of different types of WBCs as previously described by the effects of tobacco on peripheral blood hypomethylation. 72 Nonetheless, we found some hypermethylated genes in WBCs of breast cancer patients including APC, HDAC1, BRCA1, and GSK1 whose hypermethylation pattern has been previously reported in more than one studies of breast cancer tissues. Replication of the same gene methylation pattern in different sample types and patients' race may highlight the critical epigenetic changes of those genes toward their under-expression leading to cancer progression.…”
Section: Discussionmentioning
confidence: 89%
“…However, we cannot exclude the possibility that the overlap of gene expression and DNA methylation change in relation to smoking may be due to changes in white blood cell types. A recent study by Bauer et al suggested that smokingrelated differential methylation and expression of GPR15 results from the enrichment of a smoking-induced lymphocyte population (42).…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated convincingly by Bauer et al (2015), 76 associations of small changes in DNA methylation of specific loci associated with environmental exposures can be explained by exposure-associated changes in the leukocyte composition. The authors show that smoking-associated alterations of a CD3 lymphocyte subtype explain the reports by multiple authors of tobacco-associated DNA methylation alterations at the GPR15 locus.…”
Section: Implications For Population-based Research and Therapeuticsmentioning
confidence: 97%